Ming dai fan wang yu dao jiao wang chao jing ying de zhi du hua hu jiao = Ming prince and Daoism : institutional patronage of an elite - Wang, Richard G. (Guang hua wen shi wen xian yan jiu cong shu, 2019)
Summary in vernacular field only